MODEL LATIHAN DRIBBLE SEPAKBOLA UNTUK PEMULA - Subakti; Hermansyah; Nurdin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
The research objective was to create an effective model in the development of dribble training in soccer for beginners. This development research uses a research and development model approach or Research and Development (R&D) from Brog and Gall. The number of samples for the small group trial was 24 players and the large group used 30 players with the technique (purposive random sampling). The results showed that the dribble training model in the small group trial stage stated that the product developed could be done but with the trainer's instructions or still under guidance. Meanwhile, the results of large group trials state that the product developed can be applied and accepted by athletes without any difficult guidance or testing. In the development product effectiveness test, it shows that there is a difference between the pretest and posttest after being given treatment of 4.29167. Meanwhile, the very strong contribution and relationship of dribble training to the ability to dribble was 65.93%. t-test obtained a number of 12.708 df = 23 and a p-value = 0.000 <0.05, which means that there is a very significant difference between before and after the dribble training model treatment, dribble combination passing, and dribble combination shooting. Thus, the development of a dribble model item combination of passing and shotting is feasible and can be used in football. Tujuan penelitian adalah untuk membuat model yang efektif dalam pengembangan latihan dribble pada cabang olahraga sepakbola bagi pemula. Penelitian pengembangan ini menggunakan pendekatan model penelitian dan pengembangan atau Research and Development (R&D) dari Brog dan Gall. Jumlah sampel untuk uji coba kelompo keci sebanyal 24 pemain dan kelompok besar menggunakan 30 pemain dengan Teknik (purposive random sampling). Hasil penelitian menunjukkan bahwa model latihan dribble pada tahap uji coba kelompok kecil dinyatakan bahwa produk yang dikembangkan dapat dilakukan akan tetapi dengan instruksi pelatih atau masih dalam pembimbingan. Sedangkan pada hasil uji coba kelompok besar menyatakan bahwa produk yang dikembangkan sudah dapat diterapkan dan diterima oleh atlet tanpa adanya pembimbingan atau ulangan yang menyulitkan. Pada uji efektifitas produk pengembangan menunjukkan adanya selesih antara pretest dan posttest setelah diberikan perlakuan sebesar 4.29167. Sedangkan kontribusi dan hubungan yan sangat kuat latihan dribble terhadap kemampuan menggiring bola sebesar sebesar 65.93%. uji-t didapatkan angka sebesar 12,708 df = 23 dan nilai p-value = 0.000 < 0.05 yang berarti terdapat perbedaan yang sangat signifikan antara sebelum dan sesudah adanya perlakuan model latihan dribble, dribble kombinasi passing, dan dribble kombinasi shooting. Dengan demikian, pengembangan item model dribble kombinasi passing dan shotting layak dan dapat digunakan dalam sepakbola.